169k views
1 vote
How do I solve this I need help ASAP

How do I solve this I need help ASAP-example-1
User Ickster
by
6.4k points

1 Answer

4 votes

Answer:

16, -3

Explanation:

Set the equation to 0: x^2-7x-6x-48=0

Simplify: x^2-13x-48=0

Find what multiplication of 48 adds up to 13. -16 multiplied by 3 is equal to 38, so that's the two terms we must separate in the equation.

We end up with x+3x-16x-48=0

Now we can factor out x by multiplying (x+3): x(x+3)-16(x+3)=0

(x+3)(x-16)=0

Now take the opposites and you get x=16,x=-3 as your answer

User Biswajit Karmakar
by
6.3k points